Health data from diaries used in low-income communities, north India. - Kumar, Neeta; Adhikari, Tulsi; Singh, Jiten Kh; Tiwari, Nidhi; Acharya, Anita S. (Bulletin of the World Health Organization, 2021)
Objective To determine the acceptability of keeping a self-written health diary among members of low-income communities, with the aim of generating needed health data. Methods We identified three different types of impoverished communities (tribal, inner-city slum and rural) in north India, and conducted a baseline survey to establish the sociodemographic properties of the members of 595 (tribal), 446 (slum) and 51 (rural) households. We designed health diaries with a single page to fill in per month, each with a carbon duplicate, and distributed diaries to willing participants. Health volunteers visited households each month to assist with diary completion and to collect duplicate pages for a period of one year. We compared the frequency of illnesses reported in health diaries with baseline survey data. Findings A total of 4881 diary users (tribal: 2205; slum: 2185; rural: 491) participated in our project. In terms of acceptability, 49.6% (1093/2205), 64.7% (1413/2185) and 79.0% (388/491) at the tribal, slum and rural sites, respectively, expressed satisfaction with the scheme and a willingness to continue. In the tribal and slum areas, we observed increased reporting of illnesses from health diaries when compared with baseline data. We observed that influenza-like illnesses were reported with the highest frequency of 58.9% (2972/5044) at the tribal site. Conclusion We observed high levels of acceptability and participation among the communities. From our initial field studies, we have observed the benefits to both our study participants (timely preventive education and referrals) and to service providers (obtaining health data to allow improved planning).